Conversational Implicature in Wolfgang Borchert’s Short Story Die Küchenuhr: A Gricean Pragmatic Study - Priskila Yosefina Natalia Sinaga; Risnovita Sari (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2026)
This study analyzes conversational implicature in Wolfgang Borchert’s short story Die Küchenuhr using Grice’s pragmatic theory. The study is motivated by the minimalist style of German postwar literature, in which simple utterances often contain deep implied meanings. This research aims to identify forms of conversational maxim flouting in the main character’s utterances and explain the implicatures generated by those floutings. The study employed a descriptive qualitative method with documentation and note-taking techniques. The data consisted of selected utterances of the main character that contain maxim flouting and implied meaning. Data were analyzed using Grice’s Cooperative Principle, which includes the maxims of quantity, quality, relevance, and manner, supported by an interactive analysis model involving data reduction, data display, and conclusion drawing. The findings show that all four maxims are flouted, with quantity and relevance appearing most prominently. The implicatures reveal longing for the mother, regret over neglected simple moments, and belated awareness of lost happiness.